Give the trauma patient what they bleed, when and where they need it: establishing a comprehensive regional system of resuscitation based on patient need utilizing cold‐stored, low‐titer O+ whole blood. (13th April 2019) - Zhu, Caroline S.; Pokorny, Douglas M.; Eastridge, Brian J.; Nicholson, Susannah E.; Epley, Eric; Forcum, Jason; Long, Tasia; Miramontes, David; Schaefer, Randall; Shiels, Michael; Stewart, Ronald M.; Stringfellow, Michael; et al.
Abstract : BACKGROUND: Despite countless advancements in trauma care a survivability gap still exists in the prehospital setting. Military studies clearly identify hemorrhage as the leading cause of potentially survivable prehospital death. Shifting resuscitation from the hospital to the point of injury has shown great promise in decreasing mortality among the severely injured. MATERIALS AND METHODS: Our regional trauma network (Southwest Texas Regional Advisory Council) developed and implemented a multiphased approach toward facilitating remote damage control resuscitation. This approach required placing low‐titer O+ whole blood (LTO+ WB) at helicopter emergency medical service bases, transitioning hospital‐based trauma resuscitation from component therapy to the use of whole blood, modifying select ground‐based units to carry and administer whole blood at the scene of an accident, and altering the practices of our blood bank to support our new initiative. In addition, we had to provide information and training to an entire large urban emergency medical system regarding changes in policy. RESULTS: Through a thorough, structured program we were able to successfully implement point‐of‐injury resuscitation with LTO+ WB. Preliminary evaluation of our first 25 patients has shown a marked decrease in mortality compared to our historic rate using component therapy or crystalloid solutions. Additionally, we have had zero transfusion reactions or seroconversions. CONCLUSION: Transfusion at the scene within minutes of injury has the potential to save lives. As our utilization expands to our outlying network we expect to see a continued decrease in mortality among significantly injured trauma patients.